Beneficial effects of the novel marine oxygen carrier M101 during cold preservation of rat and human pancreas. Issue 12 (11th October 2019) - Lemaire, Florent; Sigrist, Séverine; Delpy, Eric; Cherfan, Julien; Peronet, Claude; Zal, Franck; Bouzakri, Karim; Pinget, Michel; Maillard, Elisa
Abstract: Ischaemia impairs organ quality during preservation in a time‐dependent manner, due to a lack of oxygen supply. Its impact on pancreas and islet transplantation outcome has been demonstrated by a correlation between cold ischaemia time and poor islet isolation efficiency. Our goal in the present study was to improve pancreas and islet quality using a novel natural oxygen carrier (M101, 2 g/L), which has been proven safe and efficient in other clinical applications, including kidney transplantation, and for several pre‐clinical transplantation models. When M101 was added to the preservation solution of rat pancreas during ischaemia, a decrease in oxidative stress (ROS), necrosis (HMGB1), and cellular stress pathway (p38 MAPK)activity was observed. Freshly isolated islets had improved function when M101 was injected in the pancreas. Additionally, human pancreases exposed to M101 for 3 hours had an increase in complex 1 mitochondrial activity, as well as activation of AKT activity, a cell survival marker. Insulin secretion was also up‐regulated for isolated islets. In summary, these results demonstrate a positive effect of the oxygen carrier M101 on rat and human pancreas during preservation, with an overall improvement in post‐isolation islet quality.